Γενική απογραφή του πληθυσμού του Ναυπλίου κατά το 1825 - Ρέππας, Χρ. (2023)
Christos Κ. Reppas: General Census of the Population of Nauplia in 1825. Summary. The first attempts for the census of the population during the Greek Revolution of 182|l are examined in the introduction of this study, down to the year 1825, on the basis of unpublished mainly documents. During the two years 1824-1825 an acute problem of population had been created in Nauplia, on account, of the abundant influx in it of every class population (soldiers, politicians, refugees, weak people and foreigners) from all the parts of Greece, especially after the holo¬caust of Mesologi, the continuation of the war and the activities of the Egyptians. In the 2nd chapter of the Study the situation in Nauplia is exami¬ned. This exactly situation compeled the government to proceed to two partial and one general census of the population in one year. The results of the last general census was a list of 10.276 inhabitants. The analytical, nominative and numerical lists obtained by that census are contained in this study, including the relevant indications (family composition, age, professional occupation). In an Anex documents are edited and a nominative table, of the second and last census of August 1825, is published. The material used is derived from the Ministry of the Police 1823-1825, which is keeped the General Archives of the Greek State.